The integration of digital technology in construction project management / Chiew Wei Jie - Chiew , Wei Jie (2025)
The construction industry in Malaysia is navigating a pivotal digital transformation, as underscored by initiatives like the Construction Industry Transformation Programme (CITP) and the Construction 4.0 Strategic Plan. This research explores the integration of digital technologies in project management within this sector, emphasizing current adoption levels, challenges, and strategies for improvement. Utilizing qualitative methods, including semi-structured interviews with industry experts, the study uncovers insights into tools like Building Information Modelling (BIM), the Internet of Things (IoT), and extended reality (XR). Key findings highlight the advantages of these technologies in enhancing collaboration, efficiency, and safety. BIM serves as a central platform for stakeholders, promoting unified project understanding and streamlined communication. IoT facilitates real-time monitoring, resource management, and safety enhancements, while XR offers immersive visualizations for risk identification and design refinement. Despite these benefits, significant barriers persist, including high initial costs, limited ROI evidence, and workforce skill gaps. Resistance to change and the reliance on conventional methods further hinder widespread adoption. The research proposes actionable recommendations, including fostering stakeholder understanding, integrating technologies into cohesive platforms, and prioritizing upskilling initiatives. These measures aim to enhance the industry's readiness for digital transformation, ensuring sustainable productivity improvements and competitive growth. The findings provide valuable insights for policymakers and industry leaders seeking to leverage digital innovation in construction project management.